Hedge Funds and Financial Market Dynamics - Jansen, Anne (Occasional Papers; Occasional Paper ;, 1998)
Hedge funds are collective investment vehicles, often organized as private partnerships and resident offshore for tax and regulatory purposes. Their legal status places few restrictions on their portfolios and transactions, leaving their managers free to use short sales, derivative securities, and leverage to raise returns and cushion risk. This paper considers the role of hedge funds in financial market dynamics, with particular reference to the Asian crisis.